O desenvolvimento profissional de professoras iniciantes mediante um grupo colaborativo de trabalho - Montalvão, Eliza Cristina (Universidade Federal de São Carlos, 2008)
The early years of professional activity are the period in which new graduates face the challenge of completing their transition from students to teachers. Research has shown that this phase is characterized by intense learning and significant stress, often in unfamiliar contexts where the beginners are required to attain professional skills while maintaining a certain level of personal balance (Marcelo, 1998). Many interfering factors will affect the daily routine of beginning teachers, frequently leading to a number of obstacles to overcome. This work applies a qualitative approach in the detection and resolution of such difficulties from a collaborative perspective, using workgroup cooperation as a central strategy. It also investigates the contribution of workgroup strategy to the development of beginning teachers, and to the beginners ability to face and overcome arising problems. Theoretical references were taken from previous studies on the recent trends in teacher development, the knowledge basis of teaching and the processes of pedagogic reasoning. Collaborative research was performed with a group of four beginning elementary school teachers who attended weekly meetings over a one-year period. The full-length transcripts of all meetings served as the main source of pertinent data, supplemented by several written accounts produced by the participants themselves. Results show that, among the several challenges encountered by teachers in their day-to-day activities, classroom management issues can be considered as the primary source of difficulties. The group was effective in proposing solutions to reported problems and in contributing to the professional development of beginners. Works of this nature, however, can be limited by a number of factors, such as the time span between the establishment of a group and the moment it becomes truly collaborative (Grossman et al, 2001). Despite that fact, the group used in this study rendered meaningful results and showed that the theorization of day-to-day classroom experiences can constitute a powerful instrument for the professional development of teachers.
Keywords: Pesquisa colaborativa; Educação - formação; Professores iniciantes; Formação continuada; Collaborative research; Beginning teachers; Teacher education; Continuous development; CIENCIAS HUMANAS::EDUCACAO